2014
DOI: 10.13080/z-a.2014.101.034
|View full text |Cite
|
Sign up to set email alerts
|

Potential of industrial hemp (Cannabis sativa L.) genotypes to suppress weeds

Abstract: Field experiments designed to explore weediness of hemp crops of industrial varieties were carried out at the Upytė Experimental Station of the Lithuanian Research Centre for Agriculture and Forestry in 2010-2012. Eight monoecious industrial hemp varieties from France (5), Poland (2) and Ukraine (1) were grown in a conventional crop rotation after winter wheat. Hemp was sown at a seed rate of 50 kg ha -1 with 10 cm interrows at the beginning of May and harvested when the first matured seeds appeared. No mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
3
4
0
Order By: Relevance
“…Hemp crop weediness at harvesting time was much lower than that at the beginning of vegetation (Tables 5 and 4), but still abundant (12-23 plants m -2 ). Similar amount was found at harvest in previous our investigations [20]. Perhaps, rainy period was favourable not only for hemp growing, but for weeds as well.…”
Section: Resultssupporting
confidence: 91%
“…Hemp crop weediness at harvesting time was much lower than that at the beginning of vegetation (Tables 5 and 4), but still abundant (12-23 plants m -2 ). Similar amount was found at harvest in previous our investigations [20]. Perhaps, rainy period was favourable not only for hemp growing, but for weeds as well.…”
Section: Resultssupporting
confidence: 91%
“…Comparable results were reported byCampiglia et al (2017),Papastylianou et al, (2017) andTang et al, (2016) who found that high N fertilization had a positive impact on hemp biomass. In addition, as reported by other studies, cultivars 'Futura 75' and 'Fedora 17' showed higher biomass yield and weed competitiveness compared to the early cultivar 'Uso 31' under contrasting environments and management practices(Sausserde et al, 2013;Jankauskiené et al, 2014;Tang et al, 2016).…”
supporting
confidence: 69%
“…As a result, the opinion that weed control in hemp is usually unnecessary, specially under high crop densities, has been expressed by a number of researchers (Struik et al, 2000;Campiglia et al, 2017). However, other studies suggest that weed control is essential for high crop yields when hemp is grown for seed or at low plant densities (Jankauskiené et al, 2014;Flessner et al, 2019). Although these latter studies provide indication that weed infestation in early crop growth can cause severe yield losses in hemp, information on crop interaction with weed communities of local agro-ecosystems under different types of cultural management is very scarce (Sandler and Gibson, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Jankauskien≐ et al . () evaluated the potential suppression of weeds by eight monoecious hemp cultivars in Lithuania and reported relatively high weed densities (133–202 plants m −2 depending on year) that the authors hypothesised stemmed, in part, from environmental conditions. At hemp harvest, greatest weed densities existed in plots with cultivars USO 31, the variety with the shortest growth period and plant height, and Beniko, a variety considered to mature early, and the authors suggested that early flowering could potentially limit canopy development and, therefore, the ability of the crop to suppress weeds (Jankauskien≐ et al ., ).…”
Section: Resultsmentioning
confidence: 99%